KESULTANAN TERNATE DAN TIDORE - Rusdiyanto Rusdiyanto (IAIN Manado, 2018)
Abstract. The history of Islam in Maluku including the history of the entry and development of Islam among various other countries up to now is still very interesting to be studied, given the history or history agreed by researchers and observers of Islamic history. This paper describes Islam in Maluku in the framework of two major sultanates of its time namely the Sultanate of Ternate and Tidore Sultanate. Based on the search on the limited this paper shows: First, the Sultanate of Ternate and Tidore is a great Islamic kesulturasi in Maluku which intersect with a major sultanate in the archipelago that has a major role in the process of Islamization in Maluku. Second, the success of Islamization in Maluku mostly uses the term through Islamization culture in Java. Third, the Islamization Process begun from the elite accounts of the kingdom/sultanate, followed by the people. Keywords: Maluku, the Sultanate of Ternate, Tidore, dan Islamization Abstrak. Sejarah Islam di Maluku sebagaimana sejarah masuk dan berkembangnya Islam di belahan wilayah Nusantara lain hingga kini masih menarik untuk diteliti, mengingat belum adanya titik terang atau rumusan sejarah yang disepakati oleh peneliti dan pemerhati sejarah Islam. Paper ini memaparkan tentang Islam di Maluku dalam bingkai dua kesultanan besar pada masanya yaitu Kesultanan Ternate dan Kesultanan Tidore. Berdasarkan penelusuran pada sumber yang terbatas tulisan ini menunjukkan bhwa: Pertama, Kesultanan Ternate dan Tedore merupakan kesultan besar Islam di Maluku yang setara dengan kesultanan besar lain di Nusantara yang memiliki peran besar dalam proses islamisasi di Maluku. Kedua, Keberhasilan Islamisasi di Maluku banyak dipengaruhi karena ditempuh melalui pendekatan budaya sebagaimana Islamisasi di Jawa. Ketiga, Proses Islamisasi itu dimulai dari kalangan elit kerajaan/kesultanan yang selanjutnya diikuti oleh rakyat. Kata Kunci: Maluku, Kesultanan Ternate, Tidore, dan Islamisasi